Development of lean environmental management intergration system for sustainbility of ISO 14001:2004 Standard - Robert@Kerk, Swee Tian (UTeM, 2016)
Nowadays, organizations are rapidly taking measures in integrating Environmental Management System (EMS) and lean practices in all types of environmental conditions in order to enhance their performance and efficiency. The main objective of this study is to propose a model that provides an EMS by integrating of ISO 14001:2004 standard with the lean principles that ensures the continuous improvement and sustainability for the organization in the current environment. This study develops the conceptual framework for EMS through integrated lean principles with ISO 14001. The developed model will be known as “Lean Environmental Management Integration System” (LEMIS). The developed framework will be tested in order to provide the conclusion to the study. This study conducts quantitative research to identify the answers for proposed objectives. Here, questionnaire is designed and provided to 140 managers from various organizations in Malaysia. The collected data is be tested by using SPSS tools. The findings of the study confirm that, successful integration of EMS, lean principles and ISO 14001 brings various advantages to the entire organization including employees, stakeholders, community, and customers. LEMIS performance measurement model was developed to visualize all the performance measures and involvement of all levels of employees to enhance the problem solving capability. The case study in real life implementation were used for results validation. Visual indicators helps the field workers avoid the repetition of past problem and only noticing the symptoms and quickly responded and take preventive actions. This study concludes that, integration of EMS and lean principles with ISO 14001 have ability to enhance the performance and efficiency of the organization.